Sosialisasi Alat Tanam Benih Jagung Berbasis Double Seed Hopper Di Kecamatan Pegagan Hilir - Purba, Jhon Sufriadi; Sinaga, Mardame Pangihuta (STMIK Royal, 2024)
The process of planting corn using conventional methods that have been happening in the community so far has become a problem faced by partners. As a result, the corn planting process takes a long time due to the stages of land preparation, seed placement, and corn covering not occurring simultaneously. By providing training and direct assistance to partners on the use of corn seed planting tools, it can improve their understanding and skills in using the tool effectively. By conducting socialization methods to provide understanding to partners with the aim of the community understanding the use of corn seed planting tools based on the double seed hopper and understanding how to maintain the tool. Thus, with this tool, the corn seed planting process becomes faster. Corn planting is the most widely produced crop in the world, and corn seed plants are most suitable for planting in high-temperature areas. Especially in Indonesia, corn plants cover more than 100 million hectares, consisting of 70 countries and even 53 developing countries. The tool being socialized is a simple tool that is used with human power by pushing without the use of motorized equipment. In the planting process, the spacing between corn seed plants and the number of corn seeds can be adjusted during the planting process. The vessel or container supplying corn seeds is a hopper located at the top, and a hole is provided at the bottom of the hopper, which is the outlet channel. Thus, the results of this socialization can shorten the time in the corn seed planting process. Keywords : corn seed; produktif; corn seed planting tool; hopper; maintenance